The chemistry of three indigenous seeds, and the extraction, nutritional and industrial potentials of their oils - Asante, Frank Adu (2011)
A thesis submitted to the Board of Postgraduate Studies, University of Science and Technology in partial fulfilment for the requirements for the award of Master of Philosophy in Biochemistry.